Opportunities and Challenges for Shaping Ecological Safety in the Times of the Coronavirus Pandemic. The European Perspective - CZUBA, Michał (Journal of Environmental Management and Tourism; Vol 11 No 8 (2020): JEMT Volume XI Issue 8(48) Winter 2020, 2020)
Earth is a dynamically changing planet, permanently shaped by the interactions between human activity and the natural environment. The phenomena occurring in nature overlap with human activities, which leads to the emergence of threats to both humanity and the natural environment itself. The result of these overlapping processes are disasters. The current coronavirus pandemic can be described as a catastrophe, the measure of which is the increasing number of people dying of this disease and the complications that occur as a result of it. However, this situation has albeit unintentionally, exerted an influence on the state of the natural environment and the level of ecological safety. The cognitive goal of this article is to try to determine these influences, particularly the positive ones. Its practical goal is to propose actions and ideas to sustain positive changes related to ecological safety after the coronavirus pandemic. The above article was based on so-called desk research. The sources of information used to create it were materials, reports and analyses available on the Internet and in the press. Research carried out in this way is of a qualitative nature and has determined the potential impacts of the coronavirus pandemic on ecological safety. The weakness of the conducted research is the limited time associated with obtaining the materials and information used, as well as the limited predictability regarding the situation related to the occurrence of Covid-19 in Europe and in the world. The considerations presented in the text refer, to a large extent, to European countries. They are illustrated with short case studies. An important part of this article are the solutions it offers that are useful in practice for national governments, including those who are members of the European Union, to maintain positive effects on ecological safety resulting from the coronavirus pandemic.